NMDAR inhibitor preconditioned mesenchymal stromal cell-derived extracellular vesicles enhance post-stroke recovery by targeting excitotoxicity and neuronal regeneration - Zhang, XiaoLu; Tian, HuanNa; Bo, HaiMei; Zhong, Li (Frontiers in Cellular Neuroscience, 2025)
BackgroundStroke is a leading global cause of disability and mortality, with ischemic stroke triggering NMDAR overactivation and excitotoxic neuronal injury. Extracellular vesicles (EVs) derived from stem cells under specific microenvironmental conditions show therapeutic potential for stroke recovery.Materials and MethodsPhotothrombotic stroke was induced in male ICR mice, followed by intravenous administration of EVs from memantine-preconditioned human umbilical cord mesenchymal stem cells (HUC-MSCs; M-EV). Behavioral outcomes were assessed using modified neurological severity scores (mNSS) and Morris water maze tests. Tissue damage was evaluated via TTC staining, Evans blue extravasation, and immunofluorescence. PCR-array analysis identified neuronal regeneration pathways. In vitro, oxygen-glucose deprivation (OGD)-challenged HT22 hippocampal neurons were co-cultured with M-EV to assess viability, migration, and apoptosis.ResultsM-EV outperformed conventional EVs in functional recovery, with miR-139-5p and miR-133b identified as key miRNAs enriched in M-EV, mediating neuroprotective effects. M-EV treatment activated neuronal regeneration pathways and reduced infarct volume. In OGD models, M-EV enhanced HT22 neuron viability, promoted migration, and suppressed apoptosis.ConclusionMemantine-preconditioned EVs (M-EVs) exhibit superior neurorestorative capacity via miRNA-mediated mechanisms, offering a promising translational approach for stroke therapy. The study highlights the potential of microenvironment-tailored EVs in neural repair.